Frequency of Heart Failure in Patients Thrombolysed for Acute Interior Wall Myocardial Infarction - Najam Ul Hassan; Yousaf , Muhammad Ehtisham; Syed Jalal Ud Din; Haq , Samra; Talha , Muhammad; Naseeb Ullah; kakar , Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: With inferior wall myocardial infarction (IWMI) making up a sizable percentage of cases, myocardial infarction (MI) continues to be a major cause of morbidity and mortality globally. A common treatment for ST-elevation myocardial infarction (STEMI) is thrombolytic therapy, which aims to decrease the size of the infarct and restore coronary blood flow. Methods: 200 patients with acute IWMI receiving thrombolytic treatment participated in this cross-sectional study, which was carried out at the Bolan Medical Complex Hospital in Quetta. In order to ensure representation across various demographics and comorbidities, patients were chosen through the use of purposeful sampling. Clinical case reviews, study of hospital records, and patient interviews were used to gather data. Descriptive statistics were used to examine the prevalence of heart failure, related risk factors, and treatment results. Results: According to the study, 40% of patients who had thrombolysis for IWMI went on to develop heart failure. Fatigue (45%) decreased exercise tolerance (55%), and dyspnea (60%) were the most commonly reported complaints. The three main comorbidities that were found were smoking history (45%), diabetes mellitus (40%), and hypertension (50%). 25% of patients needed to be readmitted to the hospital, and 30% of patients had recurrent symptoms even after receiving thrombolytic therapy. Nonetheless, 75% of patients said they were generally satisfied with their care. Conclusion: Heart failure is still a frequent and serious side effect of thrombolytic treatment for acute IWMI. Key risk factors included smoking, diabetes mellitus, high blood pressure, and advanced age. Although thrombolysis improves outcomes, a considerable number of patients continue to experience symptoms and require readmission. To lessen the burden of heart failure in this patient population, these findings emphasize the necessity of enhanced post-thrombolysis monitoring, early intervention, and focused management techniques.